Pelatihan Perakitan Komputer dan Instalasi Software Dalam Meningkatkan Kemandirian Remaja di Desa Karangturi Banyumas - Mohammad Imron; Kuat Indartono (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Human resource development has always been an important part in developing nation and state. Younger generation is one of the human resources who need more attention. Karang Taruna is a social organization in the development forum for the younger generation. It grows and develops in the village. Karangturi village is one of 19 villages in Sumbang sub-district. 50% of the village population at productive age do not have soft skills as a support in the era of the industrial revolution 4.0. And the village operators who works for village require soft skills to ease the work. The aims and solutions offered from training in community service programs are to provide computer assembly training and software installation to support the performance of the Karangturi Village government. The method used is by conducting observations, interviews, providing training and evaluation by giving questionnaires to participants. The results of the training that was carried out for 2 days with a duration of 5 hours for each meeting, the training went well and could improve the soft skills of teenagers with a value of 50% strongly agree to the training, 40% according to the training that had been carried out, and 70% of the participants stated that they understood the training materials